SME Support Policy in European Union and Baltic States: Principles and Problems - Kristiina Kasemets; Raili Kriisa; Anu Reiljan (European Regional Science Association (ERSA), 2001)
Small and medium-sized enterprises have an important role to perform in a country's economic development: they ensure free competition, decrease unemployment and balance the development of different regions. But SMEs cannot exist without a special support system. In this article, the SME support systems in the Baltic States are analyzed (with the main stress placed on Estonia), and their weaknesses are defined. As the Baltic States intend to join the European Union, it is also important for their SME support systems to be compatible with the overall SME support policy of EU. This issue will also be analyzed in the article, and the main differences between the SME support policies in EU and the Baltic States will be brought out to suggest an advisable course of SME policy development in the Baltic States.
Keywords: 330